Legal Protection Against Indonesian Umrah Jemaah - Salman Maggalatung (Jurnal Cita Hukum, 2017)
Implementation of Umra in Indonesia has increased significantly in recent years. It is caused by better condition of the economy in Indonesia so that raising the awareness of the Indonesian people to do the Sunnah that they believed. Therefore, it has become the obligation of the government to facilitate the implementation of Hajj and Umra to be good and not harm for Indonesian pilgrims. This is important because in some cases many problems occur and harm both morale and material to the Indonesian people. Therefore, clear and definite legal instrument are needed to protect the rights of pilgrims as consumers of Hajj and Umra. Pelaksanaan Ibadah umrah di Indonesia dari tahun ke tahun mengalami peningkatan yang signifikan. Hal ini didorong dengan semakin baiknya kondisi perekonomian di Indonesia sehingga meningkatkan kesadaran masyarakat Indonesia untuk menjalankan ibadah Sunnah yang diyakininya. Oleh karena itu sudah menjadi kewajiban pemerintah memfasilitasi penyelenggaraan ibadah haji dan umrah agar pelaksanaannya menjadi baik dan tidak merugikan kepada calon jamaah Indonesia. Hal ini penting dikarenakan pada beberapa kasus banyak masalah yang terjadi dan merugikan baik moril maupun materil kepada jamaah. Untuk itu diperlukan perangkat hukum yang jelas dan pasti agar melindungi hak-hak jamaah sebagai konsumen penyelenggaraan ibadah haji dan umroh. DOI: 10.15408/jch.v5i1.6582Implementation of Umra in Indonesia has increased significantly in recent years. It is caused by better condition of the economy in Indonesia so that raising the awareness of the Indonesian people to do the Sunnah that they believed. Therefore, it has become the obligation of the government to facilitate the implementation of Hajj and Umra to be good and not harm for Indonesian pilgrims. This is important because in some cases many problems occur and harm both morale and material to the Indonesian people. Therefore, clear and definite legal instrument are needed to protect the rights of pilgrims as consumers of Hajj and Umra. Implementation of Umra in Indonesia has increased significantly in recent years. It is caused by better condition of the economy in Indonesia so that raising the awareness of the Indonesian people to do the Sunnah that they believed. Therefore, it has become the obligation of the government to facilitate the implementation of Hajj and Umra to be good and not harm for Indonesian pilgrims. This is important because in some cases many problems occur and harm both morale and material to the Indonesian people. Therefore, clear and definite legal instrument are needed to protect the rights of pilgrims as consumers of Hajj and Umra.